2012
DOI: 10.1007/s12603-012-0407-3
|View full text |Cite
|
Sign up to set email alerts
|

“It could probably help someone else but not me”: A feasibility study of a snack programme offered to meals on wheels clients

Abstract: Objectives Community-based services, such as Meals on Wheels (MOW), allow older adults to remain in their homes for as long as possible. Many MOW recipients experience decreased appetite that limits intake at mealtimes. This pilot study aimed to determine the feasibility of providing high protein high energy snacks to improve nutrient intakes of MOW clients in a regional centre of New South Wales, Australia.Participants A convenience sample of 12 MOW clients.Intervention Participants received snacks five times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…In the present study, many participants ate less than they used to, concurring with previous research ( 27,46–49 ) . Some participants appeared to have an almost obsessive adherence to eating behaviours that they felt would keep them healthy and independent; for example, emphasising the amount of fruit, skimmed milk and breakfast cereals they ate, or how little they ate.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, many participants ate less than they used to, concurring with previous research ( 27,46–49 ) . Some participants appeared to have an almost obsessive adherence to eating behaviours that they felt would keep them healthy and independent; for example, emphasising the amount of fruit, skimmed milk and breakfast cereals they ate, or how little they ate.…”
Section: Discussionsupporting
confidence: 92%
“…However, further research is required to investigate additional fortified options and uptake over a longer time frame. Provision of an additional daily mid‐meal snack may be another useful addition to existing MOW services; however, a pilot study identified that not all MOW consumers at risk of malnutrition perceive that snacks are beneficial for them …”
Section: Discussionmentioning
confidence: 99%
“…MOW services have been shown to be effective in improving older adults’ nutritional status, and offering a good alternative for older adults who have limited ability to cook and prepare meals . Charlton et al . reported increased energy and protein intakes as well as an improved MNA score with MOW clients after four weeks of receiving nutrient‐dense snacks provided through the existing service.…”
Section: Discussionmentioning
confidence: 99%